Assessment of Various Skin Diseases in Patients Visiting Dermatology Department - Illa, Naga Sridevi; Pendiyala, Pradeep (Asian Journal of Medical Research, 2019)
Background: To assess various skin diseases in patients visiting dermatology department. Subjects and Methods: One hundred eighty patients visiting dermatology department with various skin diseases was recorded. The diagnoses were classified as per the international classification of diseases (ICD 10). A detailed cutaneous examination was recorded. When necessary, laboratory investigations, skin tests, and biopsy specimen findings were recorded. Results: Out of 180 patients, males comprised 110 (61.1%) and females 70 (38.9%). Age group 20-40 years comprised of 35, 40-60 years had 70 and 60-80 years had 75 cases. Various dermatoses recorded were hair disorders (15) such as alopecia areata in 10, hair fall in 5, papulosquamous (25) such as psoriasis in 12, lichen planus in 7, pityriasis rosea in 4 and lichen nitidus in 2. Sweat & Sebaceus gland disorder (90) such as miliaria in 30 and acne in 60. Pigmentary (50) such as vitiligo in 25, freckles in 15 and mongolian spot in 10 cases. The difference was significant (P< 0.05). Conclusion: Common dermatoses recorded was sweat & sebaceus gland disorder such as miliaria and acne.